A tuning point in plant acoustics investigation. (3rd August 2021) - Allievi, Sara; Arru, Laura; Forti, Luca
ABSTRACT: In a very recent book called Sensory Biology of Plants, published by renowned publisher Springer Nature, the authors stated that the scientific literature gathered so far regarding knowledge around the field of Plant Acoustics allows us to divert the focus from the question "whether plants perceive sound" toward the questions "how and why they are doing it" Some phenomena are well known: roots perceive the sound of flowing water and display a sound-mediated growth toward the water source, while the buzz pollination process allows plants to minimize the pollen lost and maximize which is collected by true pollinators. But plants are far more perceptive and responsive to their environment than we generally consider them to be, and they are communicating far more information than we realize if we only took all their signals (VOCs, sound, exudates, etc.) into a greater picture. Could Volatile Organic Compounds (VOCs) be involved in mediating more responses than we imagine? VOC synthesis and release is known to be elicited also by electrical signals caused by mechanical stimuli, touching and wounding being among these, serving as info-chemicals in the communication between plants ("eavesdropping"), and within the organs of the same plant, in order for it to get synchronized with its surroundings. This paper is an overview of the discoveries around plant perception with a focus on the link between mechanical stimuli, as sound vibrations are, and changes in plant physiology leading to VOC emission.